Implementation of the SEKUL (Sejarah Keluarga) Learning Model Through Oral History: A Systematic Approach to Improving Social-Emotional Competence - Handoyo, Intan Cahyaning; Utami, Indah Wahyu Puji; Widiadi, Aditya Nugroho (Universitas Negeri Malang, 2025)
This research aims to develop an oral history-based SEKUL (Sejarah Keluarga) Learning Model in improving the social-emotional competence of SMA Negeri 4 Malang students. The problem identified is the limited attention of history learning to the development of empathy, social awareness, and relational skills of students. The research used the Dick and Carey Model systematic approach, including identification of instructional objectives that combine cognitive and social-emotional mastery, analysis of skill components (interview techniques, transcription, context interpretation), development of operational performance objectives, and instrument development: interview rubrics, communication observation sheets, and reflective journal formats. Instructional materials and strategies were prepared with oral history guide modules, interview simulations, and focused discussions. The final stage was a summative evaluation involving cognitive pre-tests and post-test, reflective journal analysis, and standardized interviews. Results showed significant improvement in five CASEL domains: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. In addition to mastery of historical facts, students reported increased self-confidence, active listening skills, and awareness of the family's cultural context. The findings confirm that the SEKUL Model facilitates meaningful history learning by integrating academic and character-building objectives, thus recommending its integration into the secondary level history curriculum.